Loris Malaguzzi, un pédagogue contemporain - Emilie Dubois (Recherches en Éducation)
The city of Reggio Emilia, in the North of Italy, has been the scene of an unusual preschool experience since 1963. A real network of thirty-four municipal early childhood services (infant-toddler centers and preschools) has been created by instituting a characteristic education, often described as an alternative education. Loris Malaguzzi (1920 – 1994), the founder of this approach, really inspired by the greatest figures of the Progressive Education, always in search of how it is possible to realise his educational dream, in the vanguard of the scientific research, has been caring on a real struggle to provide the children of his town with high quality preschool services. So, who really was this character, protagonist of this great pedagogical success?